Mass education, global capital, and the world the theoretical lenses of István Mészáros and Immanuel Wallerstein - Griffiths, Tom G.; Imre, Robert (Palgrave Macmillan, 2013)
"Immanuel Wallerstein and István Mészáros are prolific scholars whose analyses of global capitalism in crisis offer distinctive insight for research across the social sciences. This book engages readers with their main theses, encouraging the application of these in our analysis of social reality and as its mass educational institutions. Griffiths and Imre undertake this task in their presentation of work under the capitalist world-economy, and the official function of mass education to prepare workers for the global economy. They develop a timely and provocative critique of mass education for this century, challenging readers to contribute to the construction of radical alternatives"..
Includes bibliographical (pages 167-184)references
Keywords: Mészáros, István, -- 1930-; Wallerstein, Immanuel Maurice, -- 1930-; EDUCATION / General; EDUCATION / Organizations & Institutions; EDUCATION / Philosophy & Social Aspects; Erziehung; Education -- Economic aspects; Capitalism and education; Labor and globalization; Human capital; Education -- Aims and objectives